Anatomical pathways and functional implications of the rodent auditory system-basal ganglia interconnectivity - Tomioka, Ryohei; Takemoto, Makoto; Song, Wen-Jie (Frontiers in Behavioral Neuroscience, 2025)
Sound influences motor functions and sound perception is conversely modulated by locomotion. Accumulating evidence supports an interconnection between the auditory system and the basal ganglia (BG), which has functional implications on the interaction between the two systems. Substantial evidence now supports auditory cortex and auditory thalamus inputs to the tri-laminar region of the tail of the striatum (tTS) in rodents. Thalamic input modulates the response gain of striatal neurons, whereas cortical input shapes their frequency tuning. Only recently has our understanding of BG projections to the auditory system advanced. GABAergic neurons in the tTS, which receive input from the auditory cortex, project to the posterior globus pallidus external segment (GPe). Posterior GPe, in turn, sends strong GABAergic projections to the non-lemniscal auditory thalamus (NLAT) and moderate projections to the cuneiform nucleus (CnF). The BG and auditory system are thus interconnected at multiple levels, forming a loop circuit in which the auditory system projects to the striatum and receives BG output via the NLAT. This circuit may mediate BG influence on auditory processing; however, the absence of motor cortex input to the tTS raises questions about its role in movement-related modulation of auditory responses. Given that the NLAT serves as a neural substrate for sound-cued aversive associative learning, BG output to the NLAT may influence learning processes. The pathway connecting the auditory system and CnF via the BG may underlie rhythmic entrainment in healthy individuals and therapeutic effects of rhythmic cues on gait in Parkinson’s disease.